Relación entre la composición de especies del género de lutzomyia frança (diptera: psychodidae, phlebotominae) y los diferentes tipos de bosques en Panamá - Valderrama C., Anayansi; Herrera, Martha; Salazar, Aleyda (Instituto de Ecología, A.C., 2008)
The species of the genus Lutzomyia França are transmitters of the cutaneous leishmaniasis and mucocutaneous in Panama. His distribution is related to the incidence of cases in rural adjacent places to forest, nevertheless the presence of the vectors can register in some areas, without it precence of cases of the illness. This study realized in the localities of Gamboa, Altos de Campana and AltoChagres, during the year 2000 to 2001 in tropical forest in Panamá. The specimens were captured by CDC trap and moved to the Commemorative Institute Gorgas where there were realized the identifications of the species and the count of the number of individuals. There were captured 8,213 individuals of the genus Lutzomyia, L. ylephiletor (Fairchild & Hertig) (1097 individuals), followed by L.carpenteri (Fairchild & Hertig) (610 individuals), and L. dysponeta (Fairchild & Hertig ) (595 individuals). The analysis Correspondence in species of Lutzomyia was related to the types of forests of the areas. In the similarity between three area the results showed that the composition of species of Phlebotominae is presented by Altos de Campana and Alto Chagres SSo= 0.503. The investigation has allowed updating the information of some genera and species of medical interesting in the studied area, with the intention of taking preventive measures and of control to avoid the proliferation of the Leishmaniasis in these areas.